Pengaruh Model POGIL (Process Oriented Guided Inquiry Learning) Pada Materi Minyak Bumi di kelas XI SMA Negeri 2 Tondano - Fatima, Adelheit; Waworuntu, Freetje; Lombok, John Z. L. (General Chemistry Journal, 2024)
The aim of this research is to determine the influence of the POGIL (Process Oriented Guided Inquiry Learning) model on petroleum material in class XI SMA Negeri 2 Tondano. The type of research used is Quasi Experimental with a research design namely one group pretest-posttest design. The sample in this study was all students in class XI/B class 1, totaling 20 people. In this research, the data collection instrument was a multiple choice test with 20 questions in accordance with the material being taught, namely Petroleum. For data analysis in this research, validity and reliability tests were used. The research results show that the average student learning outcome on the pretest is 44.5, while the average student learning outcome on the posttest is 76.5. Based on the N-gain Score Test, the N-gain value obtained is 0.561 and overall the criteria are quite effective. In the N-gain score, there is 1 student in the low category with a percentage of 5%, there are 14 students in the medium category with a percentage of 70% and 5 students in the high category with a percentage of 25%. From the N-gain results, it can be concluded that the POGIL (Process oriented guided inquiry learning) model has an effect on improving student learning outcomes in petroleum material.